2000
DOI: 10.1086/317246
|View full text |Cite
|
Sign up to set email alerts
|

Resolved Spectroscopy of the Narrow‐Line Region in NGC 1068. III. Physical Conditions in the Emission‐Line Gas

Abstract: The physical conditions in the inner narrow-line region (NLR) of the Seyfert 2 galaxy NGC 1068 are examined using ultraviolet and optical spectra and photoionization models. The spectra were taken with the Hubble Space T elescope Space Telescope Imaging Spectrograph (STIS), through the slit, 0A .1 ] 52A .0 covering the full STIS 1200È10000waveband. The slit was centered on a position north of the A 0A .14 optical continuum peak (or "" hot spot ÏÏ) at a position angle of 202¡, bisecting the brighter part of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
66
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 53 publications
(83 reference statements)
12
66
1
Order By: Relevance
“…We assumed typical conditions for the [O III] emitting region in the NLR, e.g. a hydrogen number density of 10 4 cm −3 (see Kraemer et al 2000b;Kraemer & Crenshaw 2000), a column density of 10 21 cm −2 (which ensured that the models were radiation bounded), and solar abundances (e.g. Grevesse & Anders 1989).…”
Section: Luminosity Comparisonmentioning
confidence: 99%
“…We assumed typical conditions for the [O III] emitting region in the NLR, e.g. a hydrogen number density of 10 4 cm −3 (see Kraemer et al 2000b;Kraemer & Crenshaw 2000), a column density of 10 21 cm −2 (which ensured that the models were radiation bounded), and solar abundances (e.g. Grevesse & Anders 1989).…”
Section: Luminosity Comparisonmentioning
confidence: 99%
“…At a lower spatial resolution than NaCo, both mechanisms have been proposed. Kraemer & Crenshaw (2000b) found that the central source is able to produce coronal lines. However, they also found evidence for an additional ionizing source, which could be the UV-X radiation generated by fast shocks (∼1000 km s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…determined that emission lines from the ILR of NGC 4151 could arise in the same gas responsible for the UV and soft X-ray absorption. In photoionization modeling studies of the NLR in NGC 4151 (Kraemer et al 2000), NGC 1068 (Kraemer & Crenshaw 2000a, 2000b, Mrk 3 ), and Mrk 573 ), in order to account for the strength emission lines such as [Ne v] λ3426 and [Fe v] λ6087, we argued for the presence of relatively highly ionized, e.g., logU ∼ −1, matter-bounded gas within 50 pc of the AGN. Although the column densities of these components are typically several times greater than what we have determined for components 2, 5, and 7 in NGC 4051, they span the same range in U.…”
Section: Radial Distances and Density Constraintsmentioning
confidence: 99%